Experiences of professionalized Chilean dental educators. A qualitative study - Héctor Oñate; Jaime Segovia-Chamorro; Roberto Cárcamo; Alejandra Bravo (Universidad de Concepción., 2021)
Introduction: The active learning process is certainly one of the most complex challenges in dental education. It is essential for the development of critical thinking and clinical skills. There is evidence of the need for teacher professionalization, but there is scarce literature reporting on the positive changes in the teaching profession based on such professionalization. The aim of the present study is to explore the experiences of the pedagogical performance of professionalized educators in dentistry. Material and Methods: A qualitative study was conducted using a design based on content analysis. The sample was selected for convenience and included dentists who have completed a master's degree in teaching in higher education, who were part of the teaching staff of a dental university program and with a career experience of at least 5 years. Semi-structured interviews were conducted, with three initial dimensions: Teaching Career, Motivation for Teacher Professionalization, and Impact on the teaching-learning process. The interviews were verbatim transcribed, and content analysis was performed by the researchers using data triangulation. The research was approved by the research and ethics committee. Results: Six categories were established: Generational clash, Motivations to practice teaching, Motivations to professionalize teaching, Competences acquired after professionalization, Effects of professionalization in the classroom context, and Shortcomings of the professionalized educator. Conclusion: Professionalized dental educators show comprehensive improvements in their performance. They have developed practical competences for the specific needs of the courses they give.